Extreme work, gendered work? How extreme jobs and the discourse of 'personal choice' perpetuate gender inequality. (July 2015) - Gascoigne, Charlotte; Parry, Emma; Buchanan, David
This review sets extreme jobs in the context of the institutional, occupational, organizational and individual drivers of long hours and work intensification and identifies the consequences for gender equality, human sustainability and long-term productivity. We suggest that extreme jobs derive not from the 'nature' of managerial and professional work but from working practices and occupational discourses which have developed to suit the gendered norms of 'ideal workers'. These practices and discourses encourage long hours rather than working-hours choices. Extreme jobs extend the gendered division of labour and increase the separation of work and non-work spheres; they are a structure of gender inequality. This review suggests that future research should seek to identify alternative but business-neutral working practices which contest the extreme 'nature' of managerial and professional work, measure the social value of non-work activities and deepen our understanding of the personal and social significance of non-work identities other than motherhood, and disentangle situational motivation, work passion and workaholism as motives for devoting long hours to work so that impacts on well-being and productivity can be more clearly understood.